Ideas of uncountable objects in the literature written in ancient Greek: from meaningless occupation — to omniscience of Apollo and God - Elena Prikhodko (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
One of the prophecies of the seven astragals oracle from the Pisidian city of Termessus included the saying “to count the waves,” indicating the futility of the intended endeavor. The author seeks to ascertain the purposes behind the Greeks’ utilization of imagery pertaining to uncountable objects such as waves, grains of sand, stars, and others. Additionally, the author aims to explore the perceptions surrounding the act of counting these objects within both domestic and cultural-religious contexts. The article shows that this “incalculability” was attracted by the Greeks to express incommensurable and even opposite concepts. First, through expressions like “to count the waves”, the case was characterized as either impossible or meaningless and stupid. Secondly, countless stars or waves were recalled when there was a need to emphasize the incredibly huge number of objects being described. Third, thanks to Apollo’s revelation announced in the response of the Delphic oracle, the knowledge of the number of grains of sand and the size of the sea formed the basis of the formula of divine omniscience: “I know the number of grains of sand and the depths of the sea”. When the books of the Old Testament were translated, the Hebrew tradition began to speak in ancient Greek. In it, the uncountable objects were needed primarily to emphasize God’s promise to Abraham of the multiplicity of the Israelite people, and for comparisons as well as to describe God’s omniscience. The list of uncountable objects itself differed in part from the standards recognized by the ancient Greeks. The ancient Greek and Jewish traditions merged in Byzantine literature into a single stream of the Christian tradition. The lists of uncountable objects of both traditions have been combined and further expanded upon. The Greek tradinion’s designation for an impossible or meaningless endeavor was retained. Passages from the Old Testament with words of God’s promises to Abraham were quoted and retold. Comparison with uncountable objects was actively used. The Apollo’s revelation was recognized as a deception of this demon, torn away from Apollo and eventually given to God.